2018
DOI: 10.1186/s12889-018-5483-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and stabilizing trends in overweight and obesity among children and adolescents in China, 2011-2015

Abstract: BackgroundThe prevalence of childhood overweight and obesity in developed countries appears to be plateauing. The purpose of this study was to provide the most recent data on the prevalence and trends in overweight and obesity among Chinese children and adolescents from 2011 to 2015.MethodsWe used data collected in the China Health and Nutrition Survey (CHNS) and China Nutritional Transition Cohort Study (CNTCS). We used two waves of the survey in 12 provinces conducted in 2011 (aged 7–18 years; n = 1458) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 36 publications
5
74
3
1
Order By: Relevance
“…The pooled results of 16 included studies showed that males had a slightly higher prevalence than females, which was consistent with the results reported in some previous studies but contradictory to the results reported in other studies . The differences in the prevalence between genders observed in this study may be attributed to the latest finding that the rates of obesity and overweight are greater for males than for females in China, and obesity has been shown to be a risk factor for malocclusion . In addition, the sexual dimorphism in skeletal maturity might have contributed to the variations in the reported results.…”
Section: Discussionsupporting
confidence: 79%
“…The pooled results of 16 included studies showed that males had a slightly higher prevalence than females, which was consistent with the results reported in some previous studies but contradictory to the results reported in other studies . The differences in the prevalence between genders observed in this study may be attributed to the latest finding that the rates of obesity and overweight are greater for males than for females in China, and obesity has been shown to be a risk factor for malocclusion . In addition, the sexual dimorphism in skeletal maturity might have contributed to the variations in the reported results.…”
Section: Discussionsupporting
confidence: 79%
“…A cross-sectional study with the annual China National Nutrition and Health Survey (CHNS) [5,6,25,26] was conducted in Henan Province from September 2010 to January 2014 using a multistage stratified population-based cluster random sampling technique.…”
Section: Study Sample and Settingsmentioning
confidence: 99%
“…One of the most recent national studies reported that, in China, 42% of adults and about one-fifth of all children are overweight or obese [4]. Although changes to dietary patterns and rising obesity in Chinese adolescents and children have been reported in the nationally representative China Health and Nutrition Survey (CHNS) [5,6], malnutrition remains a threat that may hold back a generation of Chinese in certain geographic areas [7]. For instance, while China's dynamic urban population thrives, much of rural China is mired in poverty [8].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of overweight and obesity in children worldwide has resulted in a growing risk of the future burden of diabetes, hypertension, and cardiovascular disease . With the rapid economic development of China in recent years, the prevalence of childhood obesity has greatly increased . A recent study conducted in 12 provinces in 2011–2015 indicated that the prevalence of overweight and obesity among children was 11.7% and 9.0%, respectively, compared with 6.5% and 2.7%, respectively, in 2002 .…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid economic development of China in recent years, the prevalence of childhood obesity has greatly increased . A recent study conducted in 12 provinces in 2011–2015 indicated that the prevalence of overweight and obesity among children was 11.7% and 9.0%, respectively, compared with 6.5% and 2.7%, respectively, in 2002 . Identifying risk factors associated with childhood obesity may help develop early intervention strategies for prevention.…”
Section: Introductionmentioning
confidence: 99%